Evaluation of Closed System Transfer Devices in Preventing Chemotherapy Agents Contamination During Compounding Process—A Single and Comparative Study in China - Tang, YiWen; Che, XiaoTian; Wang, Yao Lei; Ye, Xin; Cao, Wan Li; Wang, Yi (Frontiers in Public Health, 2022)
Aim We performed a comparative study to investigate the efficacy of closed system transfer devices (CSTDs) on the safe handling of injectable hazardous drugs (HDs). Methods The exposure assessments of cyclophosphamide and cytarabine were performed under traditional or CSTDs. For preparation activity, chemotherapy contamination samples on protective equipment (such as gloves and masks) were collected. The contamination analysis was performed by liquid chromatography with tandem mass spectrometry (LC-MS/MS). A 6-item form was distributed monthly (form M1–M6, total 6 months) to assess the pharmacists' experience on ergonomics, encumbrance, and safety impression. Results Totally, 96 wiping samples were collected throughout the study. The numbers of contaminated cyclophosphamide samples reduced under CSTD were −37.8, −41.6, −67.7, −47.3, and −22.9% and cytarabine were −12.3, −12.1, −20.6, −69.6, and −56.7% for left countertop, right countertop, medial glass, air-intake vent and door handle, as compared to traditional devices. The reduction was similar to pharmacist devices, i.e., −48.2 and −50.0% for masks and gloves cyclophosphamide contamination, −18.0 and −42.4% for cytarabine. This novel system could improve contamination on dispensing table, transfer container, and dispensing basket by −16.6, −6.0, and −22.3% for cyclophosphamide and −28.5, −22.5, and −46.2% for cytarabine. A high level of satisfaction was consistently associated with ergonomics for CSTD during the compounding process. Meanwhile, a slightly decreased satisfaction on ergonomics, encumbrance, and safety impression was observed for the traditional system between M2 and M3. Conclusion Closed system transfer devices are offering progressively more effective alternatives to traditional ones and consequently decrease chemotherapy exposure risk on isolator surfaces.